The Relationship between Stress and Marital Satisfaction of Parents with Mental Retarded Children - Nourollah Dini-Torki; Hadi Bahrami; Abbas Davarmanesh; Akbar Biglarian (University of Social Welfare and Rehabilitation Sciences, 2007)
Objective: The purpose of this research was to study the relationship between stress and marital satisfaction of parents with educable mental retarded (E. M. R.) children. Materials & Methods: In this comparative -cross sectional study two groups of parents with E.M.R. and normal children each consists of 20 girls and 20 boys were chosen by cluster and simple randomize sampling and matched from ordinary and exceptional schools. This survey was implemented based on the Questionnaire of resources and stress, and marital satisfaction questionnaire (Enrich). The results were analysed by statistical tests such as pearson and spearman correlation, independent sample t-test and Co-Variance analysis of variance. Results: The Findings indicated that there was significant relation between stress and marital satisfaction of parents with E. M. R children (P=0/001). Also, parents of E.M.R. children in comparison with parents of normal children have more stress (P=0/001) and less marital satisfaction (P=0/021). Meanwhile, the correlation between stress and marital satisfaction was negative (r=-0.57). It means that decreasing of marital satisfaction caused by stress. Conclusion: The results revealed that the stress of educablemental retarded children's parents lead to decreasing of marital satisfaction. In other words, marital satisfaction has direct relationship with mental retarded child in the family. So, we can counsel and train to the parents of mental retarded children for reducing experienced stress.